The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/met9050583
|View full text |Cite
|
Sign up to set email alerts
|

Effects of WC Particle Types on the Microstructures and Properties of WC-Reinforced Ni60 Composite Coatings Produced by Laser Cladding

Abstract: WC-reinforced Ni60 composite coatings with different types of WC particles were prepared on 304 stainless steel surface by laser cladding. The influences of spherical WC, shaped WC, and flocculent WC on the microstructures and properties of composite coatings were investigated. The results showed that three types of WC particles distribute differently in the cladding coatings, with spherical WC particles stacking at the bottom, shaped WC aggregating at middle and lower parts, with flocculent WC particles dispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 21 publications
3
18
0
Order By: Relevance
“…Several methods for experimental testing of tribology and wear behavior of potential roll and cladding materials have been used by researchers. The majority of these methods can be roughly classified as 1) pin‐on‐disc or ball‐on‐disc tests, 2) ring‐on‐bock tests with different setups, 3) block‐on‐disc tests with or without addition of abrasive particles, and 4) disc‐on‐disc or roll‐on‐roll tests with two or even three discs or rolls, respectively. Among those test methods, in particular, the roll‐on‐roll tests are suitable to simulate the combined effects of relative motion (slip effects) and high contact pressure between the rolls of the rolling mill and the metal strip.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods for experimental testing of tribology and wear behavior of potential roll and cladding materials have been used by researchers. The majority of these methods can be roughly classified as 1) pin‐on‐disc or ball‐on‐disc tests, 2) ring‐on‐bock tests with different setups, 3) block‐on‐disc tests with or without addition of abrasive particles, and 4) disc‐on‐disc or roll‐on‐roll tests with two or even three discs or rolls, respectively. Among those test methods, in particular, the roll‐on‐roll tests are suitable to simulate the combined effects of relative motion (slip effects) and high contact pressure between the rolls of the rolling mill and the metal strip.…”
Section: Methodsmentioning
confidence: 99%
“…MMC claddings typically consist of crushed or spherical tungsten carbide particles embedded into an iron‐, cobalt‐, or nickel‐based matrix. The microstructure and the wear behavior of these claddings are generally well studied at room temperature, but only a few investigations focus on their particular wear behavior at elevated temperatures . At room temperature, abrasive wear tends to decrease with increasing hardness of the MMC cladding, i.e., with increasing content or size of the hard particles inside the matrix, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…With the purpose of establishing a relationship among three different processing parameters, that is, laser power, scanning speed and laser spot diameter, the concept of Metals 2019, 9,1245; doi:10.3390/met9121245 www.mdpi.com/journal/metals Metals 2019, 9,1245 2 of 12 average energy (E a ) [10], also called average energy per unit area [8,10,11], specific energy [12][13][14][15][16], effective energy [13,17,18] and/or energy density [10,[19][20][21][22], is frequently used in the literature; thereby, E a is basically set by adjusting the corresponding parameters. WC-Co alloys have been commonly deposited utilizing laser cladding [7,8,10,11,[23][24][25]. For example, it has been observed that laser power has a predominant effect on the LC WC-12Co alloy coating characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The use of ceramic tool materials is limited as compared with cemented carbides, although it tends to grow. It has been estimated that around 5% of cutting tool inserts are made of ceramics based on: Currently, WC-based coatings can be produced with various technologies, such as: plasma spraying [3,4], HVOF spraying [5,6], electro-spark deposited (ESD) processing [7,8], laser cladding [9,10], laser alloying [11,12], physical vapor deposition [13], chemical vapor deposition [14] and liquid state sintering in vacuum [15], which mainly fulfill protective and antiwear functions.…”
mentioning
confidence: 99%